2021
DOI: 10.1002/mrd.23529
|View full text |Cite
|
Sign up to set email alerts
|

A new hemizygous missense mutation, c.454T>C (p.S152P), in AKAP4 gene is associated with asthenozoospermia

Abstract: Asthenozoospermia (ASZ) is a condition characterized by reduced forward motility of spermatozoa affecting approximately 19% of infertile men. A kinase anchor protein 4 (AKAP4) is an X‐linked testis‐specific gene and plays a major role in sperm motility and flagella formation. However, few studies have reported its association with ASZ. Here, we sequenced for exonic mutations of human AKAP4 gene by high‐fidelity PCR/Sanger sequencing in peripheral blood samples from 150 ASZ patients and 150 fertile men. We repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…AKAP4 was also mainly expressed in the caudal fibrous sheath of spermatozoa, recruiting PKA to promote local phosphorylation and participating in the activation of the sperm flagellum. 56 A previously published study reported that a decreased level of AKAP4 expression affected sperm motility. 23 Therefore, this study concluded that it was the reason for the decreased forward motility of spermatozoa in H-DFI population.…”
Section: Discussionmentioning
confidence: 98%
“…AKAP4 was also mainly expressed in the caudal fibrous sheath of spermatozoa, recruiting PKA to promote local phosphorylation and participating in the activation of the sperm flagellum. 56 A previously published study reported that a decreased level of AKAP4 expression affected sperm motility. 23 Therefore, this study concluded that it was the reason for the decreased forward motility of spermatozoa in H-DFI population.…”
Section: Discussionmentioning
confidence: 98%
“…AKAP4 is expressed in the principal piece of the sperm flagellum and participates in the assembly of the FS 30 31. A new hemizygous missense mutation in AKAP4 has been reported to be associated with asthenozoospermia,32 but no evidence has yet been found to further confirm the hypothesised role of AKAP3 in human male infertility. Here, our genetic analyses found that homozygous deleterious AKAP3 variants led to severe asthenoteratozoospermia and male infertility.…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge suggests that AKAP4 might function beyond flagella development during spermatogenesis. Notably, variants in the AKAP4 gene have been identified in infertile males exhibiting distinct phenotypes, such as asthenozoospermia, 7 MMAF, 2 and azoospermia/NOA, 8 , 9 which shed light on the divergence of male infertility phenotypes of AKAP4 mutations.…”
mentioning
confidence: 99%